Análise microtomográfica do impacto de protocolos de agitação ultrassônica e forma de apresentação de cimentos biocerâmicos na remoção de material obturador em molares inferiores com istmo - Feitosa, Márcia Eugênia de Sousa Damasceno (2024)
The objective of the present study was to evaluate, using microcomputed tomography (microCT), the removal capacity of remaining filling material (RFM) provided by shaking protocols, passive ultrasonic irrigation (PUI) and continuous ultrasonic irrigation (CUI), in mesial roots of lower molars with isthmuses. Furthermore, verify the influence of the form of presentation of two bioceramic endodontic filling cements, This is a quantitative, ex vivo, randomized and blind study of experimental investigation in laboratory. To this end, 40 human mandibullary molars, with Vertucci II/IV type mesial roots and Hsu and Kim isthmuses II/V, were collected, scanned on microCT and prepared with instruments from the Reciproc R25 system. The teeth were randomly divided into two groups depending on the filling cement, BioRoot RCS (BCS) or Endosequence BC Sealer (ESBC), associated with gutta-percha cones using the single cone technique. After filling, the teeth were stored for 90 days (37 ºC and 100% humidity). They then had their canals unobturated with Reciproc R25 and R40 instruments. The specimens were once again taken to microCT to allow their random division between 4 experimental subgroups depending on the complementary cleaning protocol: passive ultrasonic irrigation (BCS/PUI and ESBC/PUI); and continuous ultrasonic irrigation (BCS/CUI and ESBC/CUI). The irrigating solution used throughout the study was 2.5% NaOCl; a volume of 60 mL of solution per canal was used solely in the complementary protocol. For agitation, the Irrisonic insert (E1) was used, activated in a piezoelectric device (20%), in 3 cycles of 20 seconds, the first and third cycles with 2.5% NaOCl and the second cycle with 17% EDTA. Once the irrigation/agitation steps were completed, the teeth were scanned again to determine the RFM volume. When evaluated before and after the agitating protocols, significant differences were observed in all comparisons, regardless of the filling cement used or the modality of ultrasonic activation (P < 0.05). When comparing both the agitation protocols and the filling cement, powder/liquid or pre-mixed, no significant differences were observed (P > 0.05). Concluding that the use of ultrasonic agitation proved to be effective as a complement in removing the MOR, despite not removing it completely. Furthermore, the way the filling cement was presented and the type of agitation did not influence this removal.